Reversible Thinking in Mathematical Problem Solving: An Adversity Quotient-Based Analysis of Grade VIII Students - Mar' Atus Shalehah; Yantoro Yantoro; Rohati Rohati (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Reversible thinking is the ability to reverse the order of thinking, understand two-way relationships, and logically and reflectively retrace initial information. This study aimed to describe students’ reversible thinking abilities in mathematical problem solving based on adversity (AQ). The research was conducted using a qualitative descriptive design with 21 eighth-grade students of MTs Annajah Sungai Luar. From these, five subjects were selected purposively to represent the AQ types: quitter, camper, and climber. Data were collected through AQ questionnaires, Test of Reversible Thinking (TTR) essay tasks, and interviews. The results indicated that students with the quitter type were unable to fulfill all aspects of reversible thinking. Camper-type students could fulfill two aspects, namely negation and reciprocity, while climber-type students were able to fulfill all three aspects: negation, reciprocity, and returning to the initial condition. The findings suggest that students with higher AQ demonstrate stronger reversible thinking skills in mathematical problem solving. This contributes to mathematics education by emphasizing the importance of fostering reflective thinking and resilience in the learning process.